The Role of Social Media in the Spread of Religious Extremism Thoughts and Their Impact on Social Pathology (Journal Intellectual Sufism Research (JISR), 2023)
This research aims to explore the role of social media in the spread of religious extremism and its impact on social pathology. With the development of increasingly sophisticated times, nowadays it is very easy to disseminate an idea via social media which is quickly absorbed by the public. This research will use a qualitative approach with a literature review of works relevant to the role of social media in the spread of religious extremism and its impact on social pathology. The sources used in this research are books, journals, articles and related academic writings. Content analysis of this research will be used to identify key emerging themes in the relevant literature. The results of this research reveal the role of social media in the spread of religious extremism thoughts, religious extremism from a social and transpersonal psychology perspective, as well as the impact and ways of overcoming religious extremism thoughts on social pathology. To overcome the role of social media in the spread of religious extremism, including: increasing awareness, regulation and supervision, inclusive religious education, individual awareness. Therefore, preventive and intervention steps need to be taken to overcome this problem, including increasing awareness, regulation, interfaith collaboration, inclusive education, and individual awareness.